The Influence of Classical Mythology and Its Interaction on English Literature (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
While myths have been created by people in all nations, times, and stages of civilization to explain the existence and operation of natural phenomena, to relate the exploits of gods or heroes, or to defend social or political structures, Greek mythology has continued to be the most creative and captivating source of ideas in the West.